Direction of arrival estimation of non‐Gaussian signals for nested arrays: Applying fourth‐order difference co‐array and the successive method. Issue 5 (21st September 2021) - Ye, Changbo; Chen, Weiyang; Zhu, Beizuo; Tang, Leiming
Abstract: Herein, we estimate the direction of arrival (DOA) of non‐Gaussian signals for nested arrays (NAs) by implementing the fourth‐order difference co‐array (FODC) and successive methods. In particular, considering the property of the fourth‐order cumulant (FOC), we first construct the FODC of the NA, which can obtain O ( N 4 ) virtual elements using N physical sensors, whereas conventional FOC methods can only obtain O ( N 2 ) virtual elements. In addition, the closed‐form expression of FODC is presented to verify the enhanced degrees of freedom (DOFs). Subsequently, we exploit the vectorized FOC (VFOC) matrix to match the FODC of the NA. Notably, the VFOC matrix is a single snapshot vector, and the initial DOA estimates can be obtained via the discrete Fourier transform method under the underdetermined correlation matrix condition, which utilizes the complete DOFs of the FODC. Finally, fine estimates are obtained through the spatial smoothing‐Capon method with partial spectrum searching. Numerical simulation verifies the effectiveness and superiority of the proposed method.